Impact of increasing capacity for generating and using research on maternal and perinatal health practices in South East Asia (SEA-ORCHID Project). - SEA-ORCHID Study Group (Public Library of Science (PLoS), 2011)
Background Maternal and neonatal mortality and morbidity remain unacceptably high in many low and middle income countries. SEA-ORCHID was a five year international collaborative project in South East Asia which aimed to determine whether health care and health outcomes for mothers and babies could be improved by developing capacity for research generation, synthesis and use. Methods Nine hospitals in Indonesia, Malaysia, the Philippines and Thailand participated in SEA-ORCHID. These hospitals were supported by researchers from three Australian centres. Health care practices and outcomes were assessed for 1000 women at each hospital both before and after the intervention. The capacity development intervention was tailored to the needs and context of each hospital and delivered over an 18 month period. Main outcomes included adherence to forms of care likely to be beneficial and avoidance of forms of care likely to be ineffective or harmful. Results We observed substantial variation in clinical practice change between sites. The capacity development intervention had a positive impact on some care practices across all countries, including increased family support during labour and decreased perineal shaving before birth, but in some areas there was no significant change in practice and a few beneficial practices were followed less often. Conclusion The results of SEA-ORCHID demonstrate that investing in developing capacity for research use, synthesis and generation can lead to improvements in maternal and neonatal health practice and highlight the difficulty of implementing evidence-based practice change.